Utilização do desempenho em saltos verticais na regulação da carga de treinamento - João Gustavo de Oliveira Claudino (2011)
The purpose of this study was to verify the regulating effect of the training load, using the countermovement jump (CMJ) at the beginning of the session, on the total plyometric training load and the vertical jumps performance. Forty-four males were divided in four groups: No Regulation Group (nRG), Regulation Group (RG), Yoked Group (YG) and Control Group (CG). The nRG received 6 weeks of plyometric training, with no adjustment in training load. The RG underwent the same training;however, the training load was adjusted according to the CMJ performance at the beginning of each session. The YG received the same load adjustments made for the RG. At the end of the training, the CMJ and squat jump performance of all of the participants was reassessed. The total training load was significantly lower (p = 0.036;effect size = 0.82) in the RG and the YG (1905 ± 37 jumps) compared to the nRG (1926 ± 0 jumps). The enhancement in vertical jump performance was significant for the groups that underwent the training. The nRG and the RG exhibited a large effect size (ES) in vertical jump performance; however, the YG had a moderate ES. Using vertical jump performance, performed at the beginning of the session, as a tool toregulate the training load resulted in a decrease of the total training load, without decreasing the long-term effects on vertical jump performance